Optimizing a chip kick module of a Small Size League robot - Simões, Henrique Barros; Kashihara, Guilherme; Costa, Leonardo Da Silva; Tonidandel, Flavio (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
In Small Size League (SSL), a RoboCupSoccer category, there is a high need for an optimization in a module that allows its robots to perform chip kicks in the field, this module is named after its shots: Chip kicker module. The chip kicker module can be separate in two different parts: The solenoid and electrical section, which provides force by means of a coil and a plunger, and the mechanical piece chip kicker, which transfers the force between the solenoid and the ball. In order for a proper optimization of this module, it’s necessary a deep study in physics, linear algebra, vector calculus, mechanics and electronics, a simple variation of the number of coil turns can change the entire trajectory of the ball, most of the time breaking the rules of the league.